2008
DOI: 10.1074/jbc.m802942200
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Cellular Methyl Metabolism and Adaptive Efflux during Oncogenic Transformation from Chronic Arsenic Exposure in Human Cells

Abstract: After protracted low level arsenic exposure, the normal human prostate epithelial cell line RWPE-1 acquires a malignant phenotype with DNA hypomethylation, indicative of disrupted methyl metabolism, and shows arsenic adaptation involving glutathione overproduction and enhanced arsenic efflux. Thus, the interplay between methyl and glutathione metabolism during this progressive arsenic adaptation was studied. Arsenic-treated cells showed a time-dependent increase in LC 50 and a marked increase in homocysteine (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 44 publications
(62 reference statements)
2
60
2
Order By: Relevance
“…Arsenic could affect DNA methylation due to the competitive action of DNA methyltransferases (DNMTs) and arsenite methyltransferases (AS3MT) for methyl group carried by S-adenosyl methionine. AS3MT utilizes SAM to methylate arsenite thus leading to inadequate supply of SAM to DNMTs and causing genome hypomethylation (Caudill et al, 2001;Coppin et al, 2008;Reichard et al, 2007). Some reports also point to the effect of arsenic exposure on histone modification such as H3 histone tail acetylation (Cronican et al, 2013).…”
Section: Introductionmentioning
confidence: 95%
“…Arsenic could affect DNA methylation due to the competitive action of DNA methyltransferases (DNMTs) and arsenite methyltransferases (AS3MT) for methyl group carried by S-adenosyl methionine. AS3MT utilizes SAM to methylate arsenite thus leading to inadequate supply of SAM to DNMTs and causing genome hypomethylation (Caudill et al, 2001;Coppin et al, 2008;Reichard et al, 2007). Some reports also point to the effect of arsenic exposure on histone modification such as H3 histone tail acetylation (Cronican et al, 2013).…”
Section: Introductionmentioning
confidence: 95%
“…In addition, an increasing number of experimental studies have shown that arsenic causes endocrine disruptions, change in cell cycle kinetics, epigenetic effects and change in transcription (NRC, 2001;Kitchin & Wallace, 2005;Davey et al, 2007;Reichard et al, 2007;Coppin et al, 2008).…”
Section: Introductionmentioning
confidence: 98%
“…While As-induced global DNA hypomethylation has been observed in mouse and rat liver (Okoji et al, 2002;Chen et al, 2004;Uthus and Davis, 2005) and in mammalian cells in vitro (Sciandrello et al, 2004;BenbrahimTallaa et al, 2005;Reichard et al, 2007;Coppin et al, 2008), results from the only available human population study are contradictory, showing that arsenic exposure through drinking water contamination induced a global DNA hypermethylation in a dose-dependent manner in peripheral blood leukocytes (Pilsner et al, 2007).…”
Section: Epigenomic Biomarkers Of Arsenic Exposurementioning
confidence: 97%